HUBUNGAN PENGETAHUAN PERAWAT TENTANG PATIENT SAFETY DENGAN KEPATUHAN PELAKSANAAN ASSESSMENT RISIKO JATUH RSUD KRT.SETJONEGORO WONOSOBO - Wiguna, Dika; Azuma, Anindita Paramastuti; Budiono, Soni (Jurnal Ilmiah Kesehatan, 2024)
Purpose: This study aims to analyze the relationship between nurses' knowledge of patient safety and compliance with fall risk assessment implementation. Methods: This study uses a correlational observational method with a cross-sectional design on 41 nurses in the Cempaka and Bougenvile wards through total sampling technique. Data were collected once using a questionnaire, and the relationship between variables was analyzed using the Rank-Spearman test. Results: The analysis using the Rank Spearman test with the help of SPSS version 30.0 program showed a Correlation Coefficient value of 0.440 and a p-value of 0.002. This indicates a relationship between knowledge of patient safety and compliance in conducting fall risk assessments in the Cempaka and Bougenvile Inpatient Rooms at RSUD KRT. Setjonegoro Wonosobo. The value of the correlation coefficient indicates a moderate or fairly strong relationship with a positive direction. Conclusion: There was a relationship between knowledge of patient safety and compliance with fall risk assessment implementation at RSUD KRT. Setjonegoro Wonosobo in the Cempaka and Bougenvile Inpatient Wards.